Bank and insurance capital management - De Weert, Frans. (Wiley finance series., 2011)
"The current crisis has exposed the shocking truth that very few practitioners actually understand the capital positions of banks and insurance companies, let alone have good, tried and tested methods of evaluating their capital position. The subject of capital management is deemed to be difficult but this is mainly because of the lack of a good and transparent overview rather than the complexity of the subject. It is vital to have a very clear understanding of the regulatory environment in order to earn an optimal return on capital. This book provides proven techniques for managing bank capital as well as explaining each component such as balance sheets and type of capital in depth. The book will show how to minimise risk whilst still maximising value and will also, crucially provide the regulatory context and all latest developments. Economic capital will also be discussed in depth, as will the practicalities of bank and insurance M&A. The book will also show how financial innovations can be used to optimise the capital position and how diversification effects are reflected in the capital position"--Provided by publisher.